Synthesis of Sulfonyl 2-(prop-2-yn-1-ylthio) benzo[d]thiazole Derivatives - Abbas, Mohammad A (Al-Nahrain Journal of Science, 2018)
New series of benzothiazole-2-thiol (2-MBT) derivatives were synthesized and Structures of the synthesized compounds were established on the basis of 1H NMR in DMSO- d6 and FTIR in KBr spectral data. Acetylene derivatives were prepared by the reaction of 2-MBT with 3-bromo propyne in base medium (Nucleophilic Substitution reaction- SN2) that gives (2-(prop-2-yn-1-ylthio) benzo[d]thiazole) 85% yield, these derivative was oxidized by using mixture of potassium dichromate and concentrated sulphuric acid in presence of glacial acetic acid as a solvent to give (2-(prop-2-yn-1-ylsulfonyl) benzo[d]thiazole) 72% yield.Mannich reactions were done by using (2-(prop-2-yn-1-ylsulfonyl) benzo[d]thiazole), Para formaldehyde and various secondary amines in the presence of cuprous chloride as a catalyst and dioxane as a solvent to give different derivatives 44-68% yield, and we think these compounds may have biological activity.